IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKA NARASI SISWA KELAS V SDN 127 INPRES MONCONGLOE KABUPATEN MAROS - Nurfatiha, Nabila; Munirah; Avincenna, Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low narrative writing skills of fifth-grade students at SDN 127 Inpres Moncongloe, Maros Regency. The learning process has not been engaging and has not actively engaged students. Consequently, during the orientation stage, students experience difficulty identifying problems in the story, impacting their writing skills, as they struggle to form words and construct coherent sentences. The purpose of this study is to improve the narrative writing skills of fifth-grade students at SDN 127 Inpres Moncongloe through the implementation of a problem-based learning model. This study is a classroom action research (CAR) consisting of two cycles. The subjects were 35 fifth-grade students at SDN 127 Inpres Moncongloe. Data collection techniques used included teacher and student observation sheets, narrative writing tests, and interviews with teachers and students. The results of the study showed a significant increase in students' narrative text writing skills through the problem-based learning model from the completion percentage in cycle I reaching 38.2% with an average value of 59.4 increasing in cycle II with the completion percentage becoming 91.1% and the class average reaching 73.